Legendary movies - D'Agostini, Paolo (Vercelli, Italy : White Star Publishers, 2008)
140 movies chosen from among the most beautiful, the most imaginative, the most surprising, and also the most successful in the history of cinema.
Fakulti Teknologi Kreatif dan Warisan
Includes index.
Keywords: Motion pictures -- History